WAKAF TUNAI (CASH WAQF) MENURUT PERSFEKTIF ULAMA DAN TINJAUAN MAQASHID SYARI’AH - Neni Hardiati (AKSELERASI: Jurnal Ilmiah Nasional, 2020)
Waqf is a form of worship which is a concrete example of a sense of justice. In this case, the Al-Qur'an calls it al-habs, a synonym of the word al-waqaf, namely property belonging to a person given to the public so that it can be used as long as the item remains. So, the essence of waqf lies in the form of the goods which in Islamic teachings are a continuous charity. In line with the enormous need for funds for poverty alleviation and the location is scattered outside the area of the waqifs, this has led to the idea of donating with money. With the convenience of cash waqf, people can easily spend their money to be waqf on the path of religion. The basis for waqf in the Koran is in Surah Ali-Imran verse 92, besides that, in the Qur'anic verse of Surat Al-Hajj verse 77. There is also the hadith of the Prophet Muhammad which is more explicit in describing the recommendation of waqf worship, namely the Prophet's command to Umar to donate his land in Khaibar. The Hanafi Mahzab also allows cash waqf as an exception, on the basis of istihsan bi al urfi (custom), because many people have done it. According to al Bakri, the Syafi'I school does not allow cash waqf, because dinars and dirhams (money) will disappear when they are paid so that they no longer exist. The opinion of the scholars regarding the object of waqf shows that the conditions for waqf objects (must be objects, useful, not disposable, not haram in substance and must belong to waqf perfectly). Cash waqf is not supported by hadith specifically, and uses verses from the Koran and hadiths of a general nature. Therefore, the determination of the conditions for the waqf object is included in the ijtihadi area.